Design and Implementation of the Hepatorenal Fibrocystic Disease Core Center Clinical Database: A Centralized Resource for Characterizing Autosomal Recessive Polycystic Kidney Disease and Other Hepatorenal Fibrocystic Diseases - Alzarka, Bakri; Morizono, Hiroki; Bollman, John W.; Kim, Dongkyu; Guay-Woodford, Lisa M. (Frontiers in Pediatrics, 2017)
Autosomal recessive polycystic kidney disease (ARPKD) and other hepato-renal fibrocystic diseases (HRFD) are relatively rare recessive disorders that constitute an important set of childhood nephropathies. Little is known about fundamental pathogenesis and advances toward clinical trials will require well-characterized patient cohorts as well as the development of predictive and prognostic biomarkers. Such studies in rare diseases requires greater collaboration than the efforts in common diseases where large patient repositories can be built at a single site. For the HRFD, clinical and translational research studies would be well-served by centralized case accrual that coordinates collection of clinical data, bio-specimens (DNA and tissues) and genetic information. As part of the NIH-funded Hepato-Renal Fibrocystic Disease Core Center (HRFDCC), we have established a web-accessible portal to enroll patients with ARPKD and other HRFD and compile baseline and longitudinal clinical information in a REDCap-based Clinical Database. This central database is structured to collect clinical data from patients throughout the Americas (North, Central, and South). Using informatic analyses, we have defined the first data-driven estimates of ARPKD-related neonatal mortality, as well as the incidence and prevalence of this disease. These data indicate that while ARPKD is a rare disorder, there are hundreds of patients potentially available for deep clinical phenotyping in the United States alone. The centralization and sharing of clinical information and bio-materials from ARPKD and other HRFD patients hold the potential to accelerate progress in understanding disease pathways. Once the Database is mature, the well-characterized patient cohorts will provide an important resource for developing clinical trials to evaluate new targeted therapeutic interventions in this spectrum of disorders.